The Potential of Mesenchymal Stem Cells to Treat Systemic Inflammation in Horses - MacDonald, Elizabeth S.; Barrett, Jennifer G. (Frontiers in Veterinary Science, 2020)
One hallmark of mesenchymal stem cells (MSCs) is the ability to differentiate into multiple tissue types which assist in tissue regeneration. Another hallmark of MSCs is their potent anti-inflammatory and immunomodulatory properties and the potential to treat inflammatory, immune-mediated, and ischemic conditions. In equine practice, MSCs have shown efficacy in the treatment of musculoskeletal disorders such as tendinopathy, meniscal tears and cartilage injury. However, there are many equine disease processes and conditions that may benefit from the immunomodulatory properties of MSCs. Examples include conditions associated with overwhelming acute inflammatory response such as systemic inflammatory response syndrome to chronic diseases characterized by a prolonged low level of inflammation such as equine asthma and recurrent uveitis. For the acute inflammatory response processes, there is often high morbidity and mortality with no effective immunomodulatory treatment to prevent the overwhelming synthesis of proinflammatory mediators. For chronic inflammatory disease processes, frequently long-term corticosteroid treatment is the therapeutic mainstay, with serious potential complications. Thus, there is an unmet need for alternative anti-inflammatory treatments for both acute and chronic illnesses in horses. While MSCs show promise for such conditions, much research is needed before a clinically safe and effective treatment will be available. Optimal MSC tissue source, patient versus donor source (autologous versus allogeneic) and cell growth conditions need to be determined for each problem. For immediate use, allogeneic MSC treatments is preferable, but immune tolerance and adequate safety require further study. MSC collection and cryopreservation from horses before they are injured or ill, whether from umbilical cord tissue, bone marrow or adipose might become more widespread. Once these fundamental approaches to treating specific diseases with MSCs are determined, the route of administration, dose and timing of administration also need to be studied. To provide a framework for development of MSC immunomodulatory treatments, this article reviews the current understanding of equine MSC anti-inflammatory and immunomodulatory properties and proposes how MSC therapy may be further developed to treat acute onset systemic inflammatory processes and chronic inflammatory diseases.